In situ crosslinkable hydrogels for engineered cellular microenvironments - Kyung Min Park; Ki Dong Park; V. I. Sevastianov; E. A. Nemetz; V. N. Vasilets (Вестник трансплантологии и искусственных органов, 2017)
In situ crosslinkable hydrogels have been widely used as therapeutic implants and vehicles for a broad range of biomedical applications including tissue regenerative medicine because of their biocompatibility and easiness of encapsulation of cells or signaling molecules during hydrogel formation. Recently, these hydrogel materials have been widely utilized as an artificial extracellular matrix (aECM) because of its structural similarity with the native extracellular matrix (ECM) of the human body and its multi-tunable properties. Various synthetic, natural, and semisynthetic hydrogels have been developed as engineered cellular microenvironments by using various crosslinking strategies. In this review, we discuss how in situ forming hydrogels are being created with tunable physical, chemical, and biological properties. In particular, we focus on emerging techniques to apply advanced hydrogel materials for engineered cellular microenvironments.